2016
DOI: 10.1097/sa.0000000000000244
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin Reduces Postoperative Opioid Consumption and Pain for 1 Week After Hospital Discharge but Does Not Affect Function at 6 Weeks or 3 Months After Total Hip Arthroplasty

Abstract: Background: This study examined whether a perioperative regimen of pregabalin added to celecoxib improved pain scores and functional outcomes postdischarge up to 3 months after total hip arthroplasty (primary outcome) and acute postoperative pain and adverse effects (secondary outcomes). Methods: One hundred and eighty-four patients were enrolled in a randomized, double-blind, placebo-controlled study. Two hours before receiving a spinal anaesthetic and undergoing surgery, patients received celecoxib 400 mg p.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
(19 reference statements)
0
5
0
1
Order By: Relevance
“…are preferred in acute pain, but higher doses have been associated with more adverse effects. A few studies have shown that a single preoperative oral dose of pregabalin (150 mg) can reduce postoperative pain and adverse effects in patients undergoing orthopaedic surgeries, as well as other surgeries [4,10,11]. In this study we also used the lowest effective dose of preoperative pregabalin (150 mg), which was similarly effective as doses used in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…are preferred in acute pain, but higher doses have been associated with more adverse effects. A few studies have shown that a single preoperative oral dose of pregabalin (150 mg) can reduce postoperative pain and adverse effects in patients undergoing orthopaedic surgeries, as well as other surgeries [4,10,11]. In this study we also used the lowest effective dose of preoperative pregabalin (150 mg), which was similarly effective as doses used in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that postoperative pain could persist for 2 to 6 weeks after discharge, and this could limit patient participation in daily activities [4]. Additionally, poorly controlled postoperative pain may lead to chronic pain [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gabapentin ve pregabalin multimodal analjezinin bir parçası olarak postoperatif opioid gereksinimini azaltmaktadırlar. [50,51] Preoperatif tek doz ile bu etki sağlanabilir. Anksiyolitik etkileri ek avantajlarıdır.…”
Section: Gabapentin Ve Pregabalinunclassified